Features of climate and ecological management and marketing as the basis for sustainable strategic development of a modern enterprise - Bielova, O.; Бєлова, Олена Ігорівна (Університет «КРОК», 2021)
The article is devoted to the study of the peculiarities of the formation of climate and ecological management and marketing in a modern enterprise. The terms "climate management", "ecological management" and "sustainable strategic development of the enterprise" are defined. The preconditions for the emergence and development of ecological and climate management and marketing in a modern enterprise in the process of its sustainable strategic development are identified and analyzed. Since the sustainable strategic development of the enterprise is defined in the article as a kind of socio-economic strategic development of the enterprise, carried out in harmony with the environment, it is emphasized that sustainable strategic development involves ensuring and meeting real social needs without compromising the interests of future generations, which involves the use of ecological and climate management and marketing. It is also emphasized that for the enterprise in the transition to the model of sustainable development itis necessary to ensure economically stable and further development of the enterprise due to its rational economic activity on the basis of low-waste and resource-saving technologies; as well as to promote changes in the structure of production and consumption, as there is a need to compare production with depreciation and consumption. The article defines that ecological and climate management in a modern enterprise in the process of its sustainable strategic development affects such areas as: organizational culture of the enterprise; natural resources management; waste management; security management; energy management at the enterprise; product life cycle management, etc. The article analyzes that the effectiveness of climate and ecological management and marketing also depends on such internal factors as: the level of staff qualifications; motivation of management and staff; availability of resources; level of responsibility at the enterprise. Of the external factors, the norms and laws on ecological protection at the macro level and the participation of stakeholders at the micro level are identified as key. The main advantages of climate and ecological management and marketing for sustainable strategic development of the enterprise are identified and it isemphasized that with optimally thought-out and planned implementation climate and ecological management and marketing can not only significantly increase the company's profit and production capacity, but also contributes to the formation of manifestationsof modern ecological culture, which is an integral part of sustainable strategic development of any modern enterprise

Стаття присвячена дослідженню особливостей формування кліматичного та екологічного менеджменту та маркетингу на сучасному підприємстві. Дано визначення термінів «кліматичний менеджмент», «екологічний менеджмент» та «сталий стратегічний розвиток підприємства». Визначено та проаналізовано передумови виникнення та розвитку екологічного та кліматичного менеджменту та маркетингу на сучасному підприємстві в процесі його сталого стратегічного розвитку. Оскільки сталий стратегічний розвиток підприємства в статті визначено як різновид соціально-економічного стратегічного розвитку підприємства, що здійснюється в гармонії з природним середовищем, то ставиться наголос на тому, що сталий стратегічний розвиток передбачає забезпечення та задоволення реальних соціальних потреб без шкоди інтересам майбутніх поколінь, що передбачає застосування екологічного та кліматичного менеджменту та маркетингу. Також наголошується, що для підприємства при переході на модель сталого розвитку необхідно забезпечити економічно стабільний і подальший розвиток підприємства завдяки його раціональній господарській діяльності на основі маловідходних і ресурсозберігаючих технологій; а також сприяти зміні структури виробництва і споживання, оскільки виникає необхідність порівняння обсягів виробництва з нормами амортизації та споживання. В статті визначено, що екологічний та кліматичний менеджмент на сучасному підприємстві в процесі його сталого стратегічного розвитку впливає на такі його сфери як: організаційна культура підприємства; управління природними ресурсами; управління відходами; управління безпекою; енергетичний менеджмент на підприємстві; управління життєвим циклом продукції тощо. В статті проаналізовано, що ефективність кліматичного та екологічного менеджменту та маркетингу залежить також від таких внутрішніх факторів як: рівень кваліфікації персоналу; мотивація керівництва та персоналу; забезпеченість ресурсами; рівень відповідальності на підприємстві. З зовнішніх факторів ключовими визначено норми та закони про охорону навколишнього середовища на макрорівні та участю стейкхолдерів на мікрорівні. Визначено основні переваги кліматичного та екологічного менеджменту та маркетингу для сталого стратегічного розвитку підприємства та наголошено, що при оптимально продуманому та спланованому впровадженні кліматичний та екологічний менеджмент та маркетинг може не тільки значно збільшити прибуток підприємства та виробничі потужності, але й сприяє формуванню проявів сучасної екологічної культури, яка є невід’ємною частиною сталого стратегічного розвитку будь-якого сучасного підприємства
Keywords: climate; climate management; ecological management; climate marketing; ecological marketing; sustainable development; strategy; клімат; кліматичний менеджмент; екологічний менеджмент; кліматичний маркетинг; екологічний маркетинг; сталий розвиток; стратегія